2009
DOI: 10.1364/oe.17.015716
|View full text |Cite
|
Sign up to set email alerts
|

High-speed switchable lens enables the development of a volumetric stereoscopic display

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
155
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(155 citation statements)
references
References 30 publications
0
155
0
Order By: Relevance
“…In multi-plane displays, images are drawn on presentation planes at several different optical distances for each eye, enabling both vergence and accommodation cues. These displays have been constructed using a system of beam splitters [Akeley et al 2004;MacKenzie et al 2010] and by time multiplexing with high-speed switchable lenses [Love et al 2009;] to superimpose multiple display planes additively on the viewer's field of vision (Figure 2). Many current implementations support high-resolution imagery using the full resolution of a conventional monitor, with accommodation cues that are correct for diffuse objects lying on one of the presentation planes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In multi-plane displays, images are drawn on presentation planes at several different optical distances for each eye, enabling both vergence and accommodation cues. These displays have been constructed using a system of beam splitters [Akeley et al 2004;MacKenzie et al 2010] and by time multiplexing with high-speed switchable lenses [Love et al 2009;] to superimpose multiple display planes additively on the viewer's field of vision (Figure 2). Many current implementations support high-resolution imagery using the full resolution of a conventional monitor, with accommodation cues that are correct for diffuse objects lying on one of the presentation planes.…”
Section: Related Workmentioning
confidence: 99%
“…Volumetric displays, on the other hand, present three-dimensional imagery by placing light sources at multiple optical distances, so that accommodative effects arise automatically. Stereoscopic multi-plane display architectures [Akeley et al 2004;Love et al 2009;, in particular, can present high-resolution imagery on a discrete set of presentation planes at different accommodative distances. Previous studies have shown that these displays can provide the appropriate stimuli to drive accommodation for simple, isolated, diffuse objects at intermediate distances [MacKenzie et al 2010;Ravikumar et al 2011].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial amount of research supports the idea that mitigating the vergence-accommodation conflict in stereoscopic displays improves both perception and comfort, and this observation has been a major motivation for the development of displays that support multiple focus distances (3,5,7,(12)(13)(14)(15)27). However, the fact that accommodative gain universally deteriorates with age suggests that the effects of the vergence-accommodation conflict may differ for people of different ages (28)(29)(30) and even that multifocus or dynamic display modes may be undesirable for older users.…”
Section: Resultsmentioning
confidence: 99%
“…The two dominating technologies are lenslet arrays [Lippmann 1908] and parallax barriers [Ives 1903]. Today, a much wider range of different 3D display technologies are available, including volumetric displays [Cossairt et al 2007;Jones et al 2007], multifocal displays [Akeley et al 2004;Love et al 2009], and super-multi-view displays [Takaki 2006]. Volumetric displays create the illusion of a virtual 3D object floating inside the physical device enclosure; an observer can accommodate within this volume.…”
Section: Related Workmentioning
confidence: 99%
“…Volumetric displays create the illusion of a virtual 3D object floating inside the physical device enclosure; an observer can accommodate within this volume. Multifocal displays allow for the display of imagery on different focal planes but require either multiple devices in a large form factor [Akeley et al 2004] or vary-focal glasses to be worn [Love et al 2009]. Super-multi-view displays emit light fields with an extremely high angular resolution, which is achieved by employing many spatial light modulators.…”
Section: Related Workmentioning
confidence: 99%